SUBCLINICAL RENAL DAMAGE IS ASSOCIATED WITH A REDUCED CHOROIDAL THICKNESS IN PATIENTS WITH PRIMARY HYPERTENSION. (June 2018) - Mule', G.; Vadala', M.; La Blasca, T.; Gaetani, R.; Pugliares, C.; Lattuca, L.; Terrasi, M.; Cottone, S.
Abstract : Objective: The retina is considered the easiest accessible window to study the state of the systemic microcirculation, even if the choroid is the most important vascular layer of the eye. Our understanding of the choroid has been greatly increased in last years since the introduction of advanced techniques of optical coherence tomography (OCT). Our study was aimed to assess choroidal thickness by using Swept-Source OCT (SS-OCT) in essential hypertensive patients (EHs) with and without subclinical renal damage (SRD). Design and method: We enrolled 100 EHs of which 65 without kidney damage and 35 with SRD. In all the participants SS-OCT and a routine biochemical work-up were performed. Glomerular filtration rate (GFR) was estimated by the CKD-EPI equation (eGFR). SRD was defined, by the presence of microalbuminuria or eGFR between 30 and 60 mL/min/1.73 m2. OCT measurements were performed according to the Early Treatment Diabetic Retinopathy Study (ETDRS) protocol, that divides the macula into 9 subfields. The circular grid consists of 3 concentric rings. The inner and outer rings are further divided into quadrants: temporal, nasal, superior, and inferior. Furthermore, we calculated the average of the individuals values of the four quadrants separately for the inner and the outer ring. The average of all the 9 regions of the ETRDS grid (including the inner, the outer and the central rings) was also calculated. Results: EHs with SRD showed thinner choroidal thicknesses than those without kidney damage (all p < 0.05), even after adjustment for age (figure). Overall choroidal thickness correlated significantly and directly with eGFR (r = 0.36) and negatively with urinary albumin excretion (r = - 0.39). The association of choroidal thickness with SRD was confirmed in multiple logistic regression analyses once the effect of age, anti-hypertensive therapy and triglycerides was accounted for. The odds ratio of having SRD associated with a standard deviation increase of overall choroidal thickness was 0.43 (0.24–0.75, 95% confidence interval; p = 0.007). Figure. No caption available. Conclusions: Our study confirms the close relationships between changes in ocular microcirculation and renal dysfunction.